2009
DOI: 10.1002/app.29640
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, conductivity, band gap, and kinetic of thermal degradation of poly‐4‐[(2‐mercaptophenyl) imino methyl] phenol

Abstract: The oxidative polycondensation reaction conditions of 4-[(2-mercaptophenyl) imino methyl] phenol (2-MPIMP) were studied in an aqueous acidic medium between 40 and 90 C by using oxidants such as air, H 2 O 2 , and NaOCl. The structures of the synthesized monomer and polymer were confirmed by FTIR, 1 H NMR, 13 C NMR, and elemental analysis. The characterization was made by TGA-DTA, size exclusion chromatography (SEC) and solubility tests. At the optimum reaction conditions, the yield of poly-4-[(2-mercaptophenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Unreacted monomer was separated from the reaction product by washing with CHCl 3 . The mixture was filtered and washed with hot water (3 Â 25 mL) to separate the mineral salts and then dried in the oven at 110 C. 1 …”
Section: Synthesis Of Opnmmpmentioning
confidence: 99%
See 1 more Smart Citation
“…Unreacted monomer was separated from the reaction product by washing with CHCl 3 . The mixture was filtered and washed with hot water (3 Â 25 mL) to separate the mineral salts and then dried in the oven at 110 C. 1 …”
Section: Synthesis Of Opnmmpmentioning
confidence: 99%
“…Many studies on oxidative polymerization and the reaction mechanisms of polyphenols have been reported. 1–3 Schiff‐base‐substituted oligomers or polymers, which include azomethine (CHN) and active hydroxyl (OH) groups, have been used in various fields, including electrochemical cells and materials resistant to high energy, because of their useful properties, including paramagnetism and semiconductivity. They have also been used to prepare compounds with resistance to high temperature, thermostabilizatiors, 4 graphite materials, 5 and antistatic materials.…”
Section: Introductionmentioning
confidence: 99%
“…This aspect is highly sought for reducing the number of layers required for functional devices and is not readily achievable with current conjugated materials because of the incompatibility of the highest occupied molecular orbital and lowest unoccupied molecular orbital energy levels with currently used electrodes. There are many studies reporting the synthesis of polyazomethines and their electrical properties before and after doping 3–5. For instance, Kaya et al5 showed that, by I 2 doping, the conductivity of perylene‐containing polyazomethines improved by about five orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…The decomposition kinetic parameters of Co(II), Ni(II) and Cu(II) complex with benzylamino-p-chlorophenylglyoxime ligand were studied by Arslan. 8 Also, Doğan et al [9][10][11][12] and the others 13,14 have investigated the thermal behavior, kinetic and thermodynamic parameters of various metal complexes and polymeric materials using TG/DTG and DTA.…”
Section: Introductionmentioning
confidence: 99%